Introduction to Law Enforcement and Criminal Justice, 12th Edition - Kären Hess (Cengage Learning, 2017)
This comprehensive and practical book covers law enforcement and the criminal justice system as a whole (including courts, corrections, and juvenile justice) in one easy-to-understand volume. You'll find a realistic and relevant "boots on the street" perspective, real world examples in every chapter, and up-to-date information on a wide range of today's hottest topics. You'll learn about the ways technology is changing the day-to-day operations of policing and police interaction with the public; the recommendations of the President's Task Force on 21st Century Policing, including the need to improve trust and legitimacy with the public and a shift away from the warrior mentality to a guardian mindset; the law enforcement response to new terrorism threats such as ISIS and homegrown violent extremists; drones and other new surveillance techniques; and more.